CLINICAL IMPROVEMENT IN SYSTEMIC SCLEROSIS-ASSOCIATED LOWER EXTREMITY ULCERS USING TOCILIZUMAB AND OZONE THERAPY COMBINATION: A REPORT OF TWO CASES - Yamancan, Gülşah; Kılıç, Jehat; Doğan, Yusuf; Karataş, Ahmet (My University, 2025)
The aim of this case report was to evaluate the potential efficacy of adjunctive ozone therapy combined with tocilizumab in treating refractory lower extremity ulcers in patients with diffuse systemic sclerosis (SSc). We report two female patients with diffuse SSc who developed refractory ulcers de-spite prior therapies, including azathioprine, mycophenolate mofetil, cyclophosphamide, and vasodi-lators. Both patients were receiving weekly subcutaneous tocilizumab (162 mg) when ozone therapy was introduced. The protocol consisted of major autohemotherapy with ozone (initial dose 15 µg/mL; maintenance dose 65 µg/mL), combined with ozone bagging. Treatment included 25 daily sessions, 25 twice-weekly sessions, and subsequent weekly maintenance sessions. Both patients exhibited significant ulcer healing, pain reduction, and improved mobility, suggesting synergistic effects beyond those of tocilizumab monotherapy. Refractory SSc-associated ulcers remain a therapeutic challenge. The combination of tocilizumab and ozone therapy may provide additional benefits through anti-inflammatory and microcirculatory mechanisms. Controlled trials are warranted.
Keywords: Systemic sclerosis; tocilizumab; ozone therapy; refractory ulcers